(untitled) (The Geographic Base, 2024)
Land surface temperature and vegetation indices have been explored as indicators for various environmental variables. A number of research papers have normalized difference vegetation index as an approximation of density, and urban expansion depends on normalized difference build-up index of Nepalgunj urban area ranging from 2013 to 2022. Based on Landsat 8 satellite images, it investigates impacts on thermal conditions, vegetation and settlements and retains strong trends for environmental transformation. The result obtained revealed a very strong positive relationship between LST and NDBI (r2 = 0.6042 to 0.7743), denoting a higher level of urban growth and hence an increased surface temperature. Similarly, there is a very strong negative relationship between LST and NDVI (r2 = -0.3165 to -0.5524), which shows that an increase in temperature will have a damaging effect on health of vegetation. Moreover, an inversely proportional relationship between NDVI and NDBI has been found an explicit compromise between urban expansion and vegetative cover. These results are imperative for formulating and implementing the effects of UHI.